Effects of Power-Oriented Resistance Training With Heavy vs. Light Loads on Muscle-Tendon Function in Older Adults: A Study Protocol for a Randomized Controlled Trial - Rodriguez-Lopez, Carlos; Alcazar, Julian; Losa-Reyna, Jose; Martin-Espinosa, Noelia Maria; Baltasar-Fernandez, Ivan; Ara, Ignacio; Csapo, Robert; Alegre, Luis M. (Frontiers in Physiology, 2021)
Background Power-oriented resistance training (PRT) is one of the most effective exercise programs to counteract neuromuscular and physical function age-related declines. However, the optimal load that maximizes these outcomes or the load-specific adaptations induced on muscle power determinants remain to be better understood. Furthermore, to investigate whether these adaptations are potentially transferred to an untrained limb (i.e., cross-education phenomenon) could be especially relevant during limb-immobilization frequently observed in older people (e.g., after hip fracture). Methods At least 30 well-functioning older participants (>65 years) will participate in a within-person randomized controlled trial. After an 8-week control period, the effects of two 12-week PRT programs using light vs. heavy loads will be compared using an unilateral exercise model through three study arms (light-load PRT vs. non-exercise; heavy-load PRT vs. non-exercise; and light- vs. heavy- load PRT). Muscle-tendon function, muscle excitation and morphology and physical function will be evaluated to analyze the load-specific effects of PRT in older people. Additionally, the effects of PRT will be examined on a non-exercised contralateral limb. Discussion Tailored exercise programs are largely demanded given their potentially greater efficiency preventing age-related negative consequences, especially during limb-immobilization. This trial will provide evidence supporting the use of light- or heavy-load PRT on older adults depending on individual needs, improving decision making and exercise program efficacy. Clinical Trial Registration NCT03724461 registration data: October 30, 2018.